2017
DOI: 10.2147/ppa.s132859
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life, visual function and treatment satisfaction following intravitreal dexamethasone implant for diabetic macular edema

Abstract: PurposeThe aim of this study was to explore and describe quantitatively patient-reported outcome measures (PROMs), ie, health-related quality of life (QoL), visual function and treatment satisfaction, in patients with diabetic macular edema (DME) receiving two different regimens of Ozurdex (intravitreal dexamethasone implant).MethodsIn this multicenter, prospective study, 100 patients with center-involving refractory DME were randomized 1:1 to either five monthly fixed dosing or optical coherence tomography (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…Sub-scale analysis prior to and following laser photocoagulation showed a statistically significant change in five of the 13 items of RetTSQ: overall satisfaction with current treatment, discomfort/pain, unpleasantness of treatment, patient influence on the treatment and received information about the treatment. According to Ramu et al the patients' perceived treatment satisfaction was based on their final VA status, while baseline VA and macular thickness were not found to affect RetTSQ scores [20]. Considering the statistically significant decline in the patients' post treatment visual acuity and the decrease of their TS score in our sample, it is not surprising that we found a similar result, in regard to their overall satisfaction with the treatment.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Sub-scale analysis prior to and following laser photocoagulation showed a statistically significant change in five of the 13 items of RetTSQ: overall satisfaction with current treatment, discomfort/pain, unpleasantness of treatment, patient influence on the treatment and received information about the treatment. According to Ramu et al the patients' perceived treatment satisfaction was based on their final VA status, while baseline VA and macular thickness were not found to affect RetTSQ scores [20]. Considering the statistically significant decline in the patients' post treatment visual acuity and the decrease of their TS score in our sample, it is not surprising that we found a similar result, in regard to their overall satisfaction with the treatment.…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, there is no comparable data from other studies that used the RetTSQ as we did, in patients with PDR treated with PRP. The fact that the RetTSQ has previously been employed in only a few studies [17,20] and has not been rigorously tested in more researches represents one of the main limitations of our study [25]. Further testing of RetTSQ is required to establish the usefulness of RetTSQ to measure patient satisfaction of different treatments.…”
Section: Discussionmentioning
confidence: 97%
“…There are no thresholds for clinically meaningful change for the RetTSQ. 67 However, in the validation of the RetTSQ a three-point difference was observed between those with very good visual acuity and those in the category below (five-category visual acuity variable). 38 The quality-of-life change assessed using RetDQoL did not show any difference between arms ( Table 15).…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…Current anti-VEGF treatments require frequent injections and monitoring, causing a significant burden on patients and healthcare systems, with a financial impact and reduction in patient quality of life. 128 In a 2017 report, Ramu et al 129 reported a statistically significant improvement in treatment satisfaction in patients with DME treated with dexamethasone intravitreal implants.…”
Section: Discussionmentioning
confidence: 99%